Effect of cover crops and nitrogen rates on sprinkler irrigated wheat in low altitude cerrado - Sabundjian, Michelle Traete; Arf, Orivaldo; Kaneko, Flávio Hiroshi; Meirelles, Flávia Constantino; Arf, Marcelo Valentini; Nascimento, Vagner do (Revista Ceres, 2016)
Wheat production in the Brazilian cerrado faces major challenges, especially for not being a traditionally wheat region and the occurrence of hot and dry winters. The objective of this study was to evaluate the residual effect of the previous crops corn and Urochloa ruziziensis (R. Germ & Evrard), in single cropping and intercropping, with and without seed inoculation with Azospirillum brasilense and topdress nitrogen fertilization (N), on the development and yield of wheat. The experiment was conducted in Selvíria, MS, in 2011/12. The experiment was arranged in an 8x4 factorial randomized block design, with four replications. The treatments consisted of a combination of crop residues (corn, Urochloa ruziziensis and Azospirillum brasilense) and topdress N rates (0, 30, 60 and 90 kg ha-1) applied to wheat. The following evaluations were carried out: the amount of residual vegetation cover, agronomic characteristics, yield components and yield of wheat. There were positive effects of the previous crops on the yield of the succeeding wheat crop, and the intercropping corn x Urochloa ruziziensis, with or without inoculation, was an excellent management choice; increasing N rates in topdress up to 90 kg ha-1 increased the yield of irrigated wheat, depending on the previous crop.